Pertanggungjawaban Hukum Atas Bocornya Data Pribadi Pelanggan Situs Jual Beli Online - Perthiwi*, I Gusti Agung Ayu Anggy; Sutama, Ida Bagus Putu (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The intended of this reserach is to make Indonesian citizen especially the marketplace applications users (as consumer) to raise the awareness about the importance of personal data and privacy protection while using or making any transaction at marketplace applications. This research using normative legal method. The results of this research shows that Indonesia generally has some legal regulations governing privacy policies for marketplace users, contained in Act Number 11 of 2008 concerning Electronic Information and Transactions, Act Number 8 of 1999 concerning about Consumer Protection, Act Number 7 of 2014 concerning Commercial Law and Government Regulation Number 71 of 2019 concerning Operation System and Electronic Transactio. The intentions of this study so that all marketplace users can be aware and avoid their personal data get leaked when they using marketplace